Um novo olhar sobre o uso da forma lexical "aqui", no gênero textual bate-papo por computador, à luz da teoria da estrutura retórica - Elizane Pereira Neto (2011)
The present dissertation looks on the use of the portuguese lexical form ´aqui´ in chats using the Microsoft-licensed software - MSN. It aims to identify the uses in which such form can be regarded as a locative adverb, according to the definition prescribed in the Traditional Grammar (TG), as well as those uses which cannot be explained by the TG. Therefore, the present study reveals new functions of the above form ´aqui´, such as vocative function an as discourse marker. Using a corpus made up of 65 MSN texts, the core objective of this stduy is to show the kind of rhetorical relation the form keeps between parts of the text on a macro level of organization. Based on the Rhetorical Structure Theory RST, the analysis aimed to show that the Portuguese form ´aqui´, in many of its employments, is responsible for making clear the introduction or closing of a new discursive topic, while keeping the textual coherence. Thus, the conclusion reached is that the RST can be employed in the analysis of conversational texts.